Italian standardization of the BPSD-SINDEM scale for the assessment of neuropsychiatric symptoms in persons with dementia - Pozzi, Federico Emanuele; D'Antonio, Fabrizia; Zuffi, Marta; Pelati, Oriana; Vernè, Davide; Panigutti, Massimiliano; Alberoni, Margherita; Di Maggio, Maria Grazia; Costa, Alfredo, Sindem BPSD Study Group; Tremolizzo, Lucio; Farina, Elisabetta; et al. (Frontiers in Neurology, 2024)
IntroductionBehavioral and Psychological Symptoms of Dementia (BPSD) are a heterogeneous set of psychological reactions and abnormal behaviors in people with dementia (PwD). Current assessment tools, like the Neuropsychiatric Inventory (NPI), only rely on caregiver assessment of BPSD and are therefore prone to bias.Materials and methodsA multidisciplinary team developed the BPSD-SINDEM scale as a three-part instrument, with two questionnaires administered to the caregiver (evaluating BPSD extent and caregiver distress) and a clinician-rated observational scale. This first instrument was tested on a sample of 33 dyads of PwD and their caregivers, and the results were qualitatively appraised in order to revise the tool through a modified Delphi method. During this phase, the wording of the questions was slightly changed, and the distress scale was changed into a coping scale based on the high correlation between extent and distress (r = 0.94). The final version consisted of three 17-item subscales, evaluating BPSD extent and caregiver coping, and the unchanged clinician-rated observational scale.ResultsThis tool was quantitatively validated in a sample of 208 dyads. It demonstrated good concurrent validity, with the extent subscale correlating positively with NPI scores (r = 0.64, p < 0.001) and the coping subscale inversely correlating with NPI distress (r = −0.20, p = 0.004). Diagnosis (Lewy body dementia and frontotemporal dementia), medication (antidepressants and antipsychotics), caregiver, and PwD age predicted BPSD burden on the BPSD-SINDEM scale. Caregiver coping was influenced by diagnosis (Alzheimer’s and Lewy body dementia) and benzodiazepine.DiscussionThe BPSD-SINDEM scale offers a more comprehensive approach compared to NPI, by combining caregiver ratings with clinician observations. The design of the scale allows for rapid administration in diverse clinical contexts, with the potential to enhance the understanding and management of BPSD.